PENGUATAN EKONOMI KELUARGA - Ayumiati Ayumiati (Pusat Studi Wanita UIN Ar-Raniry, 2021)
Financial management is something that is very important and should always be performed by any individual or family. Good financial management can make into a prosperous family and will never be afraid of facing economic problems. It can also minimize the risk that will happen. Wife’s role in managing the family finances is very important, because managing the family fi-nances is the privilage of women. With the rigol and compassion attitude possessed, women are expected to provide peace and comfort for the family, especially in terms of economy